The Recirculation of Negativity: Theory, Literature, and the Failures of Affirmation - Noys, Benjamin (Stasis, 2013)
The contemporary theoretical moment is dominated by “affirmationism,” as the affirming of a superior economy of excess that can inscribe and rupture any actual economy. This article reconstructs and critiques this affirmationism through an analysis of how it subordinates negativity as trapped within a restricted economy, and insists on a “savage negativity” that escapes all relation. I do so by retracing the core features of affirmationism and particularly its turn to the forces of creativity and play, figured through literature, posed against the “labor of the negative.” Probing this downgrading of “labor,” as a result of the collapse of worker’s identity, I suggest that it results in a fatal detachment of negativity from any political or social instantiation. Instead, the return to negativity must be a return to the possible relational forms of negativity that attend to the impossibility of labor within capitalism.